2016
DOI: 10.4314/ajcem.v17i4.7
|View full text |Cite
|
Sign up to set email alerts
|

A survey of malaria prevalence and antimalarial preventive measures amongst students of University of Lagos, Nigeria

Abstract: The prevalence of malaria parasite and antimalarial preventive measures among students of University of Lagos, Nigeria was carried out between November 2014 and February 2015. Blood samples were collected from 400 students (with age ranging from 15-46year) by finger pricking and analyzed microscopically and by Rapid Diagnostic Test kit. Semi-structured questionnaire probing into their knowledge of the cause of malaria, ability to recognize signs and symptoms, treatment seeking behaviour was distributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…About 86.0% students, in this study, admitted that fever was the most recognized symptoms of malaria. This is in contrast to Dejazmach, et al [20] who reported chills and shivering as most recognized symptoms but is similar to a study by Olusegun-Joseph, et al [21], who reported that a good knowledge was demonstrated by the respondent in their ability to identify symptoms of malaria, more than half of the participants identify fever, headache and weakness, chills and vomiting as signs and symptoms of malaria;. Definitely this knowledge will aid in prompt treatment of the disease at the appropriate quarters in order to prevent avoidable complications.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…About 86.0% students, in this study, admitted that fever was the most recognized symptoms of malaria. This is in contrast to Dejazmach, et al [20] who reported chills and shivering as most recognized symptoms but is similar to a study by Olusegun-Joseph, et al [21], who reported that a good knowledge was demonstrated by the respondent in their ability to identify symptoms of malaria, more than half of the participants identify fever, headache and weakness, chills and vomiting as signs and symptoms of malaria;. Definitely this knowledge will aid in prompt treatment of the disease at the appropriate quarters in order to prevent avoidable complications.…”
Section: Discussionsupporting
confidence: 86%
“…This is in tandem with Awosolu, et al [16], who reported that 26.1% of the respondents did not sleep under mosquito net at night. However, 65.7% of the study population used the long lasting insecticides and this is higher when compared with the study of conducted by Olusegun-Joseph, et al [21], who reported that 16.2% of the respondents use long lasting insecticides.…”
Section: Discussioncontrasting
confidence: 57%
“…Probing further into the practices of the study population (which is outside the scope of this present study) would have revealed if drugs were used prior to hospital visitation and as such substantiate the claim of drug reaction on the parasite. Other studies showing same trend of lower prevalence by microscopy as against RDT where both were used include that carried out in Lagos, Nigeria (Olusegun-Joseph et al, 2016) and also in Tanzanian, though among children (Sumari et al, 2017). Such results however need validation by PCR in order to ascertain the true diagnostic status of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Following the manufacturer's instruction, Care Start® P.f (Access Bio Inc, 65 Chyde Road Suite A, Somerset NJ 08873 USA, Batch number M014L04-M014M10) was used to carry out a rapid diagnosis, and those samples found positive by this preliminary test were processed further microscopically. Preparation of thin and thick blood films followed same protocol employed in our previous article (Olusegun-Joseph et al, 2016). Samples detected as microscopically positive were blindly checked by a trained microscopist at the Nigerian Institute of Medical Research, Lagos.…”
Section: Methodsmentioning
confidence: 99%
“…Malaria rapid diagnostic test (mRDT) conducted using the P. falciparum histidine rich protein II test kit (SD Bioline, Abbot US) was positive for P. falciparum while light microscopy showed parasitaemia of 21,960 parasites/µl, 14,000 parasites/µl and 10,000 parasites/µl on day 1, 2 and 3, respectively. Thick blood films prepared with 10% Giemsa was used to estimate parasite density per 200 leukocytes assuming a white blood cell count of 8000 parasites/µl as detailed in a previous study [ 9 ]. She was treated with intravenous quinine 600 mg in 500 ml of 5% dextrose /0.9% saline 8-hourly for 24 h. She also received 10 mg intravenous diazepam, 1 L of 5% dextrose saline (DS) IV infusion, 1 g ceftriaxone IV daily for 48 h, 500 mg metronidazole IV 8-hourly for 48 h.…”
Section: Case Presentationmentioning
confidence: 99%